2014
DOI: 10.1016/j.fob.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Senescence marker protein‐30/superoxide dismutase 1 double knockout mice exhibit increased oxidative stress and hepatic steatosis

Abstract: HighlightsWe generated SMP30/SOD1-double knockout (DKO) mice for oxidative stress research.SMP30/SOD1-DKO mice showed low levels of ascorbic acid and premature death.SMP30/SOD1-DKO mice exhibited high levels of oxidative stress and liver injury.SMP30/SOD1-DKO mice manifest hepatic steatosis due to decreased levels of Apolipoprotein B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…It is an active substance generated by living organisms, which can eliminate harmful materials such as free radicals produced during normal oxygen metabolism (28). It can react with oxygen free radicals to generate hydrogen peroxide (29); the latter is converted into water by the organism and excreted. Thus, SOD1 activity represents the free radical scavenging ability of the body.…”
Section: Discussionmentioning
confidence: 99%
“…It is an active substance generated by living organisms, which can eliminate harmful materials such as free radicals produced during normal oxygen metabolism (28). It can react with oxygen free radicals to generate hydrogen peroxide (29); the latter is converted into water by the organism and excreted. Thus, SOD1 activity represents the free radical scavenging ability of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Both SMP‐30‐knockout mice on a Lepr db/db background as well as SMP30/superoxide dismutase‐1 double‐knockout mice developed hepatic steatosis and presented higher levels of hepatic oxidative stress and superoxide anion radicals compared with WT mice. These findings were attributed to decreased levels of hepatic apolipoprotein B and transcription factors involved in lipid metabolism . Similarly, NASH induction by methionine and choline‐deficient diet into p53‐deficient male mice resulted in slower disease progression accompanied by lower ROS accumulation and lipid peroxidation as well as fewer apoptotic cells compared with the WT mice .…”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 96%
“…Original Article Superoxide dismutase is an antioxidant enzyme that changes superoxide anion radicals into hydrogen peroxide and molecular oxygen (22). With regard to lipid metabolism in the liver, it was shown that SOD1-knockout mice presented with increased lipid peroxidation and hepatic TG accumulation because of abnormal lipid metabolism in mouse liver (23).…”
mentioning
confidence: 99%
“…Furthermore, SOD-knockout mice hepatocytes included abnormally enlarged mitochondria (24). Kondo et al (22) reported that high levels of OS caused by defects in the antioxidant system as result of concomitant deficiency of SOD in SOD-knockout mice resulted in hepatic lipid accumulation via altered lipid metabolism.…”
mentioning
confidence: 99%